2016
DOI: 10.1002/celc.201500444
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Studies of Zinc Acetate in 1‐Ethyl‐3‐methylimidazolium Acetate for Zinc Electrodeposition

Abstract: In this paper, we report on the electrodeposition of zinc from the ionic liquid 1‐ethyl‐3‐methylimidazolium acetate ([EMIm]OAc) with various concentrations of zinc acetate [Zn(OAc)2] at 100 °C. The electrochemical behavior of zinc complexes in [EMIm]OAc was determined by cyclic voltammetry. Raman and infrared spectroscopy were employed to study the coordination of Zn2+ ions with OAc−, and it was found that upon increasing the Zn(OAc)2 concentration the intensity of the band for the free acetate anion weakened,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…[ 23,24 ] For this, the zinc ores are converted to zinc oxide (ZnO) through a series of high‐temperature procedures and then leached with sulfuric acid to produce the ZnSO 4 solution. [ 23,25 ] In the search for alternatives, Zn metal has been successfully electrodeposited from chloridoaluminate ILs, [ 26–29 ] some air‐ and water‐stable ILs, [ 30–38 ] and choline chloride (ChCl)/ethylene glycol (EG) DES. [ 39,40 ] To address the economic and environmental aspects for an application, to transfer the electrodeposition to biodegradable ILs as well as ILs that are in part or as a whole composed of naturally occurring molecules appears to be important.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] For this, the zinc ores are converted to zinc oxide (ZnO) through a series of high‐temperature procedures and then leached with sulfuric acid to produce the ZnSO 4 solution. [ 23,25 ] In the search for alternatives, Zn metal has been successfully electrodeposited from chloridoaluminate ILs, [ 26–29 ] some air‐ and water‐stable ILs, [ 30–38 ] and choline chloride (ChCl)/ethylene glycol (EG) DES. [ 39,40 ] To address the economic and environmental aspects for an application, to transfer the electrodeposition to biodegradable ILs as well as ILs that are in part or as a whole composed of naturally occurring molecules appears to be important.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if aprotic ILs are used, hydrogen evolution, which is usually encountered in the electrodeposition of active metals such as Zn in aqueous solutions, can be significantly suppressed, leading to a more controllable surface morphology and higher current efficiency. Zn has been successfully electrodeposited from the traditional Lewis acidic ILs, 7-10 the air-and water-stable ILs, 3,[11][12][13][14][15][16][17][18][19] To search a common source of Zn ions and a suitable IL for the electrodeposition of Zn metal, however, is still important.The hydrophobic RTIL 1-butyl-1-methylpyrrolidinium bis ((trifluoromethyl)sulfonyl)imide ([BMP][TFSI]) has been widely used for the study of metal and alloy electrodeposition in view of various advantages, such as wide electrochemical window, wide temperature range as a liquid, relatively high conductivity, low viscosity, high hydrophobicity, and so on. Nevertheless, a problem is always encountered when this IL is used for electrodeposition; that is the poor solubility of common metal salts, such as metal chlorides.…”
mentioning
confidence: 99%
“…Moreover, the influence of the concentration of zinc acetate in 1‐ethyl‐3‐methylimidazolium acetate ([EMIm][OAc]) on the electroreduction of Zn has been reported. In this case, reducible Zn 2+ species are present only at a high concentration of Zn(OAc) 2 in [EMIm][OAc] (e.g., ≥4 m ) . Furthermore, an influence of the AlCl 3 concentration in ILs (e.g., [EMIm][TFSA]/[Py 1,4 ][TFSA] and [Py 1,4 ][TfO], in which Py 1,4 =1‐butyl‐1‐methylpyrrolidinium) on the deposition of Al has been reported .…”
Section: Introductionmentioning
confidence: 76%
“…4 m). [24] Furthermore, an influence of the AlCl 3 concentrationi nI Ls (e.g., [ EMIm][TFSA]/[Py 1,4 ][TFSA] and [Py 1,4 ] [TfO],i nw hich Py 1,4 = 1-butyl-1-methylpyrrolidinium) on the deposition of Al has been reported. [25,26] Rocher et al and Ro-dopoulos et al investigated the Al speciation and concluded that Al deposition can occur either from [AlCl 3 (TFSA)] À or from [AlCl 2 (TFSA) 2 ] À .…”
Section: In [Emim]mentioning
confidence: 99%